Leading for learning : how managers can get business results through developmental coaching and inspire deep employee commitment - Koss, Lisa J. (Boca Raton, FL : Routledge, 2021)
People do their best work when they are motivated. This may sound obvious, but while people managers instinctively agree with the centrality of motivation at work and its impact on employee engagement, their practices do not follow. With so much "real work" to do every day, how can managers also carve out time to learn, engage, build relationships, tap motivation, encourage development, and inspire? The problem is a false dichotomy between the world of business and that of people development. What if managers were able to systematically transform everyday business issues into meaningful, developmental coaching opportunities with employees at the same time? This proven coaching approach radically shifts conversations away from either-or propositions and uses an entirely different lens: transforming business challenges by connecting them directly to employee motivation to achieve the desired business result while dramatically increasing employee engagement. And all this comes none too soon as leaders must rethink the way they lead given the modern realities of organizational life. Among them: A rapidly changing workplace and increasing uncertainty that requires a fundamental shift in the leader's approach, including the distribution of authority and the expectation that employees take responsibility for their own learning Pervasive and persistent employee disengagement, characterized by employees who no longer accept the organization's priorities at the expense of their own, whereorganizations that continue to dictate terms will find ongoing challenges with costly employee turnover and lack of engagement During the past decade, the Developmental Coaching Model has been taught across the globe in nine languages and has been enthusiastically embraced by thousands of managers while dissolving the invisible barriers that block individual and organizational development and business success.
Acknowledgments. Author. Introduction. 1 Developmental Coaching. 2 The Developmental Coaching Model. 3 Phase I: Build Trust. 4 Phase II: Contracting. 5 Phase III: Work the Idea/Issue. 6 Becoming a Manager-Coach. Epilogue. Index.
OCLC-licensed vendor bibliographic record.
Keywords: Leadership; Employee motivation; Employees -- Coaching of; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Workplace Culture